Uterine and ovarian changes during testosterone administration in young female-to-male transsexuals - Giuseppe Loverro; Leonardo Resta; Miriam Dellino; Di Naro Edoardo; Maria Arcangela Cascarano; Matteo Loverro; Salvatore Andrea Mastrolia (Elsevier, 2016)
Objective: Female-to-male transition remains a specific clinical indication for long-term testosterone administration. There is a limited number of studies dealing with the effect of androgen treatment on their female receptive targets (mainly breast and uterus) and the knowledge in this field is scarce and, sometimes, contradictory. Materials and Methods: We performed a prospective study including 12 patients aged between 20 years and 32 years, with a diagnosis of gender dysphoria, treated with parenteral testosterone administration before sexual reassignment surgery. Results: Endometrial histology revealed the presence of active endometrium in 10 cases and secretive endometrium in two cases. Multifollicular ovaries were observed in all cases of active endometrium, while corpus luteum was present in the two cases of secretory endometrium. Fibroids or hypertrophic myometrium were observed in 58% of the patients. Estrogen receptor was very high (59%) in the endometrial epithelial cells and low (17%) in the myometrium. Androgen receptor expression was modest in endometrial epithelial cells (24%) and sustained in myometrium (69%). Ki67 expression is steadily present in all uterine compartments, varying from 8% in epithelial endometrium to 2% in the myometrium. Conclusion: Our data suggest that long-term testosterone administration to female-to-male patients during reproductive age induces a low proliferative active endometrium, associated with some hypertrophic myometrial changes.